THE URGENCY OF CATEGORISING KRATOM PLANTS INTO CLASS I NARCOTICS ACCORDING TO LAW NUMBER 35 OF 2009 CONCERNING NARCOTICS - Abdul Kadir; Muhammad Rifqi Ramadhan (ZILLZELL MEDIA PRIMA, 2025)
The research entitled ‘The Urgency of Categorising Kratom Plants into Class I Narcotics According to Law Number 35 of 2009 concerning Narcotics’ with the formulation of the problem, namely the urgency of kratom plants for the Indonesian government so that they must be immediately categorised into class I and the efforts that must be taken for the Indonesian government in filling the legal vacuum due to kratom plants according to Law Number 35 of 2009 concerning Narcotics. The method used in this research is an empirical normative research method that refers to identifying the implementation of laws or rules in society, as well as in business entities with a benchmark from the law. This research uses the theoretical framework of Law Enforcement by Sudarto. The results of this thesis research are to analyse the urgency of the kratom plant for the Indonesian government based on its side effects and potential for abuse as a narcotic and to identify the prevention of the spread and abuse of the kratom plant as a narcotic by the Indonesian Government based on Law Number 35 of 2009 concerning Narcotics.